Lafoeina amirantensis (Cnidaria: Hydrozoa, Campanulinoidea), the hydroid stage of the medusa Cirrholovenia tetranema (Cnidaria: Hydrozoa, Lovenelloidea) - Migotto, Alvaro E.; Cabral, André S. (Zootaxa, 2005)
The metagenetic Lafoeina is one of the many leptothecate genera with uncertain affinities, the life cycles of its constituent species being poorly known. The genus has traditionally been recognized as belonging to the polyphyletic superfamily Campanulinoidea, family Campanulinidae, taxa that artificially group together a variety of probably unrelated species. Life-history studies are the most important method to link species that were originally based solely on medusa or polyp stage, as is the case of Lafoeina spp. Findings of Lafoeina amirantensis at the coast of São Sebastião (São Paulo, Brazil) allowed us to study its juvenile medusa and to observe new facts pertinent to the classification of the Order Leptothecata. The hydrotheca of L. amirantensis is similar to those of the genus Cuspidella, except for the absence of nematophores in the latter. The newly released medusa of L. amirantensis is similar in morphology to the young medusae of Cirrholovenia tetranema, a species belonging to the family Cirrholoveniidae (superfamily Lovenelloidea).